JOINT-STOCK COMPANIES - AS A SUBJECT OF CIVIL LAW - Khushbakova Nigora Gayrat qizi (Scholar Express Journals, 2023)
This article describes in detail the organization of the joint-stock company, the founding meeting and the charter, the founders of the company, the state registration of the company, the shares of the company, and the corporate management bodies of the company
Keywords: Joint-stock company; stock; founding meeting